1999
DOI: 10.1039/a906386b
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soft vibrational modes on our understanding of oxide surface structure

Abstract: We examine the reasons for the poor quantitative agreement between the structures predicted from the minimum energy configuration of first principles calculations and those deduced from surface xray diffraction experiments for the structure properties of the TiO 2 (110) surface. In order to confine all numerical approximations very large scale all-electron first principles calculations are used. We find a very soft, anisotropic and anharmonic surface rigid-unit vibrational mode which involves displacements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
57
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 35 publications
10
57
0
Order By: Relevance
“…Initial calculations for the surface itself 14 were performed on a 36-atom cell ͓͑1ϫ1ϫ3͒ in terms of the sixatom surface unit cell͔ using 12 k-points ͑4ϫ4ϫ1 k-point mesh͒, a mesh cutoff of 126 Ry, and an energy shift of 15 meV. We found that this gives surface relaxations in reasonable agreement with the previous ab initio calculations 11 and experiments. 6 To check the dependence of our results on the slab thickness, we also calculated the ͑1ϫ1ϫ6͒ and ͑1 ϫ1ϫ7͒ slabs, and found that the surface relaxations have converged to less than 0.01 nm ͑and much better than this in most cases͒.…”
Section: Isolated Molecules and Surfacesupporting
confidence: 71%
See 1 more Smart Citation
“…Initial calculations for the surface itself 14 were performed on a 36-atom cell ͓͑1ϫ1ϫ3͒ in terms of the sixatom surface unit cell͔ using 12 k-points ͑4ϫ4ϫ1 k-point mesh͒, a mesh cutoff of 126 Ry, and an energy shift of 15 meV. We found that this gives surface relaxations in reasonable agreement with the previous ab initio calculations 11 and experiments. 6 To check the dependence of our results on the slab thickness, we also calculated the ͑1ϫ1ϫ6͒ and ͑1 ϫ1ϫ7͒ slabs, and found that the surface relaxations have converged to less than 0.01 nm ͑and much better than this in most cases͒.…”
Section: Isolated Molecules and Surfacesupporting
confidence: 71%
“…The basic physical and electronic structure of the most stable ͑110͒ surface has been well studied both experimentally 5,6 and theoretically, [7][8][9][10][11] and now, many investigations focus on defected surfaces, especially oxygen vacancies, [12][13][14] adsorption, 10,[15][16][17] or even adsorption onto defected surfaces. 18 -20 Due to their particular relevance to catalysis, many studies have also investigated the properties of adsorbed carboxylic ͑RCOOH͒ acids on the TiO 2 (110) surface.…”
Section: Introductionmentioning
confidence: 99%
“…19 The electronic free-energy contributions can be similarly added to the cluster expansion and would likely be significant in soft phonon or surface systems. 20 In most crystalline systems at normal working temperatures, the structural and vibrational free energies dominate over the electronic free-energy contributions. Interspecies forces, obtained from first-principles calculations on local perturbations of several of the training structures' equilibrium atomic positions at varied cell volumes, are used to obtain interspecies stiffness vs length force equations applicable across concentration space.…”
Section: Vibrational Free-energy Approachmentioning
confidence: 99%
“…1 for a schematic of the bulk-terminated structure), a prototypical metal oxide surface, whose precise surface structure remains a topic of some debate [2 -4], is determined with the well-established technique of quantitative lowenergy electron diffraction (LEED-IV) [5]. Importantly, we examine the impact on the structure determination of both charge transfer in the calculation of scattering phase shifts [5], and of soft surface vibrational modes [6].…”
mentioning
confidence: 99%